The innocent sleep - McGuire, Seanan (McGuire, Seanan. October Daye novel., 2023)
Tybalt, King of Cats, was soon to set his crown aside: he had married the woman he loved; he was going to be a father. After centuries of searching for a family of his own, he had finally found a way to construct the life of his dreams, and was looking forward to a period of peace. Titania, Faerie's Summer Queen, Mother of Illusions and enemy of so many he holds dear, has other plans. She has seized control of the Kingdom, remaking it in her own image. Tybalt quickly finds himself banished, along with the Undersea and the rest of the Court of Cats. Now Tybalt must find the woman he loves in a world designed to keep her from him-- and get her to unmake the illusion she is firmly enmeshed in. -- adapted from jacket